Ultralow Co Loading Phenanthroline‐based Porous Organic Polymer as a High‐efficient Heterogeneous Catalyst for the Fixation of CO2 to Cyclic Carbonates at Ambient Conditions. Issue 11 (28th April 2021) - Zhang, Xiaofeng; Ding, Junhao; Qiu, Bo; Li, Dajian; Bian, Yunpeng; Zhu, Dandan; Wang, Shimin; Mai, Wenpeng; Ming, Shujun; Chen, Jian; Li, Tao
Abstract: The exploration of cost‐effective and efficient catalysts for the transformation of CO2 into chemicals at room temperature and low CO2 pressure is a key challenge. Here, a green synthesis method of porous organic polymer was developed, which was obtained by the Scholl coupling reaction via polycondensation of 1, 3, 5‐triphenylbenzene and 1, 10‐phenanthroline at room temperature. The polymer has a large surface area (1074 m 2  g −1 ) and exhibited excellent CO2 capture of 77.26 cm 3  g −1 at 273.15 K and 1.00 bar. After loading cobalt acetate, an ultralow Co loading phenanthroline‐based porous organic polymer was obtained with very high catalytic efficiency in TOF of 263 h −1 for the fixation of CO2 to cyclic carbonates at room temperature and atmospheric with free‐solvent, which is over six‐fold than that of a molecular analogue, 1, 10‐phenanthroline‐Co(OAc)2 . This work provided a facile, powerful, green, and efficient strategy for designing porous organic polymers as high‐efficient heterogeneous catalysts in the fixation of carbon dioxide. Abstract : POPstar ! A novel heterogeneous catalyst named as Co‐phen‐POP showing an exceptionally high catalyst activity for the cycloaddition reaction of epoxides and CO2 with solvent‐free conditions under low pressure and at room temperature was obtained at ambient temperature with the cheap triphenylbenzene and 1, 10‐phenanthroline by using a green, simple, and cost‐effective strategy.